1974
DOI: 10.1128/iai.9.1.92-94.1974
|View full text |Cite
|
Sign up to set email alerts
|

Serotyping of Chlamydia I. Isolates of Ovine Origin

Abstract: Eight chlamydial isolates of ovine origin were tested in a plaque reduction system using homologous and heterologous rooster antisera. The eight isolates could be separated into two separate immunotypes. Type 1 included isolates associated with ovine abortion and one agent recovered from the feces of an apparently normal sheep. Type 2 isolates were associated with polyarthritis and conjunctivitis. These two serotypes were not cross-reactive with several chlamydiae of avian origin. Further application of the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0

Year Published

1977
1977
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 7 publications
1
24
0
Order By: Relevance
“…Storz and his coworkers (28,32,33) showed 8 biotypes in avian and mammalian C. psittaci by analysis of morphological differences of inclusion bodies and biological effects of diethylaminoethyl (DEAE)-dextran and cycloheximide in their growth medium, and further revealed 9 immunotypes in mammalian C. psittaci by applying microimmunofluorescent test (MIF). Eb and Orfila (4) also confirmed the 2 serotypes of Schachter et al (30,31). Recently Anderson (1) reported serotyping by use of typespecific monoclonal antibodies to avian and mammalian C. psittaci.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Storz and his coworkers (28,32,33) showed 8 biotypes in avian and mammalian C. psittaci by analysis of morphological differences of inclusion bodies and biological effects of diethylaminoethyl (DEAE)-dextran and cycloheximide in their growth medium, and further revealed 9 immunotypes in mammalian C. psittaci by applying microimmunofluorescent test (MIF). Eb and Orfila (4) also confirmed the 2 serotypes of Schachter et al (30,31). Recently Anderson (1) reported serotyping by use of typespecific monoclonal antibodies to avian and mammalian C. psittaci.…”
Section: Introductionmentioning
confidence: 76%
“…Many efforts were attempted to classify C. psittaci. Schachter et al (30,31) showed 2 serotypes in mammalian C. psittaci using plaque neutralization tests. Storz and his coworkers (28,32,33) showed 8 biotypes in avian and mammalian C. psittaci by analysis of morphological differences of inclusion bodies and biological effects of diethylaminoethyl (DEAE)-dextran and cycloheximide in their growth medium, and further revealed 9 immunotypes in mammalian C. psittaci by applying microimmunofluorescent test (MIF).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies for C. psittaci immunological heterogeneity by the plaque reduction technique (33,34) and immunofluorescence (2,16,32,39) did not define the components on the outer membrane responsible for the differences observed. Furthermore, few attempts to compare the antigenic structure of this species with that of C. trachomatis have been made.…”
mentioning
confidence: 81%
“…Fraser and Berman (4) clearly demonstrated that the strains associated with EAE were antigenically different from the polyarthritis and ovine pneumonitis isolates by using purification of elementary bodies with fluorocarbon and different procedures involving marked modification of antigens. A yolk sac infectivity neutralization test (11,20) and more recently a plaque reduction test (7,8) have also been used. Isolates associated with abortion and the M0907 strain could be separated from isolates associated with polyarthritis and conjunctivitis; there was no cross-reaction between these two sero-types or with several avian strains (7).…”
mentioning
confidence: 99%
“…A yolk sac infectivity neutralization test (11,20) and more recently a plaque reduction test (7,8) have also been used. Isolates associated with abortion and the M0907 strain could be separated from isolates associated with polyarthritis and conjunctivitis; there was no cross-reaction between these two sero-types or with several avian strains (7). These two serotypes were not host specific (8).…”
mentioning
confidence: 99%